The Silent Crisis: Exploring the Correlation Between Bullying and Suicidal Tendencies Among Adolescents in Java and Sumatra, Indonesia - Dewanto, Aji Cokro; Widhowati, Siwi Sri; Ariyamang, Watcharee (Journal Evidence Of Law, 2024)
Bullying is a critical global public health issue with well-documented impacts on adolescent mental health. In Indonesia, particularly in Java and Sumatra, the high prevalence of bullying presents a significant threat to youth, who are especially vulnerable during their developmental years. This paper explores the relationship between bullying and suicidal behaviors—namely suicidal considerations, planning, and attempts—among adolescents in these regions. A quantitative research design using both bivariate and multivariate statistical techniques, comprising a sample of 7,391 students sourced from the Global School Health Survey 2015, indicates that adolescents who experience bullying are significantly more likely to engage in suicidal tendencies including suicidal considerations, planning, and attempts. The findings emphasise the necessity for targeted interventions to mitigate bullying and promote mental health for adolescents. The paper concludes with recommendations for anti-bullying policies, mental health interventions and further research.